INSTRUMEN TES KECERDASAN LOGIKA-MATEMATIKA UNTUK ANAK USIA DINI - DEWI INDRIATI, NYOMAN UTARI (Program Studi Magister Pendidikan Anak Usia Dini, 2016)
This study aims to produce an instrument Logical-mathematical intelligence test inearly childhood are valid and reliable. This research was conducted in six kindergartens inJakarta. The method used in this research is the development method adapted from Dick-Careyinstructional models and models of development Djaali-Moeljono. There are three main stagesin the development of this instrument to obtain instruments finals, namely: (1) PhaseIntroduction namely: identify problems and conduct studies theories (2) phase of productdevelopment, including designing constructs measured variables based on the theory,development dimension, indicators and grains instruments, testing the validity by experts andpanels, a revised instrument panel based on expert input and analysis and reliability testingresults. (3) Implementation Phase includes: field trials, conducted empirical test, a revisionclause instrument, obtaining final instrument and establishing guidelines for administration andscoring. Test instruments resulting from this research is the instruction sheet, item pictures andmarking sheet. The tests showed that whole grains have a significant level of <0.05, with thevalue of reliability coefficient of 0.856. The results showed that the test instrument LogicalMathematical intelligence fit for use.